Driving Under the Influence of Drug and Alcohol – results of forensic investigation of biological samples (Academic Journal of Internal Affairs, 2021)
Two separate institutes of the Hungarian Institute for Forensic Sciences (HIFS) test biological samples of drivers. The Department of Blood Alcohol & Forensic Arson Investigation determines the alcohol content of blood and urine samples, while the Department of Forensic Toxicology determines the licit and illicit drugs of the samples to determine if the driving ability of the driver concerned has been affected by the consumption of any legal or illegal substance. In this article, we summarized the results of biological samples of drivers or persons involved in traffic accidents, tested by HIFS in 2019.
Keywords: driving; influence; alcohol; medicine